2021
DOI: 10.1111/are.15544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary complex Chinese herbal medicine on growth performance, digestive enzyme activities in tissues and expression of genes involved in the digestive enzymes and antioxidant enzymes and bacterial challenge in Litopenaeus vannamei

Abstract: The purpose of this study was to evaluate the effect of complex Chinese herbal medicines (CCHM) on growth performance, digestive enzyme activity, immunity and metabolism and Vibrio parahemolyticus resistance of Litopenaeus vannamei. The 30‐day feeding experimental results indicated that dietary CCHM obviously increased the survival rate (SR), weight gain rate (WGR) and specific growth rate (SGR) of shrimp. The feed conversion ratio (FCR) was obviously reduced by the CHMM. The supplementation of CCHM could sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In this regard, Abdel-Tawwab et al ( 2020) fed common carp with multi-stimulants blend (AQUAMAX) and found that SOD, CAT, and GPx activities significantly raised, while lipid peroxidation, measured as MDA, significantly decreased with AQUAMAX supplementation up to 1.0 -5.0 g/kg diet. Zhang et al (2021) investigated the influence of complex Chinese herbal medicines (CCHM) on growth performance, digestive enzyme activity, antioxidant status, immunity, and Vibrio parahaemolyticus resistance in white leg shrimp (Litopenaeus vannamei). They discovered that SOD, CAT, and GPx activities were considerably higher in the hepatopancreas of shrimp fed a 10 g CCHM/kg diet than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Abdel-Tawwab et al ( 2020) fed common carp with multi-stimulants blend (AQUAMAX) and found that SOD, CAT, and GPx activities significantly raised, while lipid peroxidation, measured as MDA, significantly decreased with AQUAMAX supplementation up to 1.0 -5.0 g/kg diet. Zhang et al (2021) investigated the influence of complex Chinese herbal medicines (CCHM) on growth performance, digestive enzyme activity, antioxidant status, immunity, and Vibrio parahaemolyticus resistance in white leg shrimp (Litopenaeus vannamei). They discovered that SOD, CAT, and GPx activities were considerably higher in the hepatopancreas of shrimp fed a 10 g CCHM/kg diet than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the intestinal digestive enzymes of L . vannamei have revealed that complex Chinese herbal medicines improve protease, amylase, and lipase activity as well as chymotrypsin gene expression [ 6 ]; Withania somnifera aqueous extract improves amylase and lipase activity [ 33 ]; Moringa oleifera leaf extract improves protease, amylase, and lipase activity [ 27 ]; and Andrographis paniculate improves trypsin and amylase gene expression [ 3 ]. Our results demonstrated that L .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, L . vannamei fed with >5 g/kg of complex Chinese herbal medicine can promote a digestive enzyme gene expression, while >10 g/kg can increase THC [ 6 ]. This study indicated that, after L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have indicated that traditional Chinese herbal medicine possesses specific therapeutic and preventive capabilities against diseases (Zhai and Li, 2019;Zhang et al, 2021). Numerous herbs exhibit natural antipyretic and detoxifying effects and contain essential natural compounds, such as phenylethanoid glycosides, resins and their glycosides, pentacyclic triterpenoids, chlorogenic acid, iridoids, and essential oils, which play crucial roles in curing viral infections and enhancing resistance (Liao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%